Anti-pollution reverse osmosis membrane and preparation method thereof

By using a light-induced radical polymerization strategy on the surface of the reverse osmosis membrane, the membrane pollution problem is solved, the film resistance and service life are improved, and it is suitable for seawater desalination and industrial wastewater treatment.

CN119793220AActive Publication Date: 2025-04-11CHINA UNIV OF PETROLEUM (EAST CHINA)

Patent Information

Application Number
CN202510053656.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-11
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

The existing reverse osmosis membranes are easily contaminated during the separation process, resulting in reduced separation efficiency, deterioration of membrane performance, shortened service life, and increased energy consumption, limiting its further promotion in the fields of seawater desalination, industrial wastewater treatment, etc.

Method used

By grafting the zwitterionic polymer using a photo-induced radical polymerization strategy on the surface of the film, the hydrophilicity of the film surface is enhanced and a stable hydration layer is constructed, thereby improving the film's anti-pollution performance.

Benefits of technology

While ensuring membrane flux and salt retention, it can significantly improve the anti-pollution performance of reverse osmosis membranes, extend the service life of the membrane, reduce energy consumption, and simplify the production process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793220A_ABST
    Figure CN119793220A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of reverse osmosis membranes, and particularly discloses an anti-pollution reverse osmosis membrane and a preparation method thereof.The preparation method comprises the steps that organic amine and organic acyl chloride are used for conducting interfacial polymerization reaction on a bottom membrane to prepare a polyamide layer; the photoinitiator containing amino or phenolic hydroxyl reacts with acyl chloride groups left on the polyamide layer after interfacial polymerization, and the photoinitiator is introduced into the surface of the film; pouring a zwitterionic solution on the surface of the membrane at a constant speed, and irradiating under ultraviolet to initiate a polymerization reaction; performing heat treatment on the membrane in a drying oven to obtain the anti-pollution reverse osmosis membrane. The zwitterionic polymer is efficiently grafted on the surface of the membrane by utilizing a photo-initiation free radical polymerization strategy, compared with a traditional grafting method, the operation process is simple, the grafting speed is high (within 5min), the use of an organic solvent is reduced, and the prepared reverse osmosis membrane has excellent anti-pollution performance and huge industrial application potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of reverse osmosis membranes, and in particular to an anti-pollution reverse osmosis membrane and a preparation method thereof. Background Art

[0002] Water pollution and water shortage are major challenges currently faced, posing a major threat to the sustainable development of the global economy and ecological environment. Polyamide reverse osmosis membranes play an important role in seawater desalination, brackish water treatment, industrial wastewater treatment, and drinking water production due to their good separation performance, chemical stability, and high separation accuracy. However, the separation process is often accompanied by membrane fouling, which leads to reduced separation efficiency, deterioration of membrane performance, shortened service life, and increased energy consumption, which have become bottlenecks restricting its further promotion.

[0003] Studies have shown that influent water quality, operating conditions and membrane surface characteristics have a significant impact on membrane fouling. At present, a variety of solutions have been developed to alleviate membrane fouling: feed liquid pretreatment, improved operating conditions, membrane chemical cleaning, etc. However, the above measures will increase operating costs and cause irreversible membrane damage. Therefore, the development of anti-fouling reverse osmosis membranes can fundamentally alleviate the membrane fouling problem and overcome the bottleneck of industrial applications.

[0004] Membrane fouling is mainly related to the interfacial interaction between pollutants and membrane surfaces. Membrane surface characteristics, such as hydrophilicity, roughness and charge density, have an important influence on pollutant-membrane interaction. Among them, the hydrophilicity of the membrane surface plays a leading role in improving the anti-fouling performance of the membrane. Most pollutants are hydrophobic. The more hydrophobic the membrane surface is, the easier it is for pollutants to approach the membrane due to the existence of hydrophobic interaction forces, and adsorb or deposit on the membrane surface, leading to membrane fouling. A highly hydrophilic membrane is conducive to the formation of a hydration layer on the membrane surface, which prevents pollutants from directly contacting the membrane surface. It can also reduce the adsorption of hydrophobic pollutants, greatly reducing the tendency of membrane fouling. Zwitterions contain both cation and anion pairs, which can bind multiple water molecules through electrostatic action to form a thicker and more stable hydration layer, which can effectively prevent the adsorption of pollutants and improve the anti-fouling performance of the membrane.

[0005] At present, the introduction of zwitterions on the membrane surface mainly adopts the surface grafting method. Surface grafting is connected by covalent bonds, and there is no problem of firmness. Surface grafting can be divided into grafting to the main chain method and grafting from the main chain method. The former mainly introduces the target polymer to the membrane surface through residual acyl chloride or pre-reaction to introduce reaction sites. The method is simple, but due to the limited number of active functional groups on the membrane surface and the spatial repulsion of the pre-grafted polymer material, the grafting is uneven and has a low coverage rate. For the grafting from the main chain method, the reversible addition-fragmentation chain transfer polymerization strategy and atom transfer radical polymerization strategy are commonly used. Its biggest advantage is that the reaction is controllable, and the composition, length and structure of the grafted polymer can be precisely controlled. However, the reversible addition-fragmentation chain transfer polymerization strategy and atom transfer radical polymerization strategy have complex and time-consuming reaction processes and harsh reaction conditions. It is difficult to apply them to the continuous production process of polyamide reverse osmosis membranes, which is not conducive to industrial scale-up. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a method for preparing an anti-pollution reverse osmosis membrane, which uses a simple and efficient photoinitiated free radical polymerization strategy to graft zwitterionic polymers on the membrane surface, enhance the hydrophilicity of the reverse osmosis membrane surface, build a stable hydration layer on the membrane surface, and improve the anti-pollution performance of the existing reverse osmosis membrane. The technical solution adopted by the present invention is:

[0007] A method for preparing an anti-pollution reverse osmosis membrane comprises the following steps:

[0008] (1) Fixing the base film on the frame, applying the organic amine aqueous monomer solution on the surface of the ground film and letting it stand, then pouring out the excess aqueous solution, and blowing the residual aqueous solution on the surface of the base film dry with an air knife;

[0009] (2) pouring the organic acid chloride oil phase solution onto the membrane surface obtained in step (1) to carry out interfacial polymerization reaction to form a cross-linked polyamide separation layer, pouring out the residual oil phase solution, and washing the unreacted organic acid chloride monomer with an organic solvent;

[0010] (3) pouring a photoinitiator solution onto the surface of the film prepared in step (2) to react with the residual acyl chloride, then pouring off the excess photoinitiator solution and blowing off the water droplets on the surface with an air knife;

[0011] (4) pouring a zwitterionic aqueous solution onto the membrane surface obtained in step (3), and irradiating the grafted zwitterionic polymer under ultraviolet light, then pouring off the excess zwitterionic aqueous solution, and washing the membrane surface with deionized water;

[0012] (5) The membrane obtained in step (4) is heat-treated in an oven to obtain an anti-pollution polyamide reverse osmosis membrane.

[0013] Preferably, in step (1), the organic amine aqueous phase monomer is m-phenylenediamine, and the standing time is 3 to 5 minutes; wherein the mass concentration of the m-phenylenediamine used is 0.1 to 10%.

[0014] Preferably, in step (1), the base membrane is one of a polysulfone ultrafiltration membrane, a polyethersulfone ultrafiltration membrane, a polyimide ultrafiltration membrane, a polyacrylonitrile ultrafiltration membrane, a polyethylene ultrafiltration membrane or a polypropylene ultrafiltration membrane.

[0015] Preferably, in the step (2), the organic acid chloride is at least one of trimesoyl chloride, terephthaloyl chloride, phthaloyl chloride, pyromellitoyl chloride, malonyl chloride, glutaryl chloride, and fumaryl chloride; the organic solvent is at least one of n-hexane, cyclohexane, n-heptane, toluene, Isopar-G, Isopar-E, Isopar-H, Isopar-L, and Isopar-M. The mass concentration of the organic acid chloride oil phase solution is 0.01-2%.

[0016] Preferably, in step (2), the polymerization reaction time is 10 to 300 seconds.

[0017] Preferably, in step (3), the photoinitiator is at least one of benzophenone-type photoinitiators such as benzophenone, 4-hydroxybenzophenone, 4-aminobenzophenone, 4,4-dihydroxybenzophenone or 4,4-diaminobenzophenone; wherein the mass concentration of the photoinitiator used is 0.1 to 10%.

[0018] Preferably, in step (3), the reaction time of the photoinitiator and the acyl chloride is 10 to 150 seconds.

[0019] Preferably, in step (4), the zwitterion is at least one of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonatepropyl)ammonium hydroxide, methacryloyloxyethyltrimethylammonium chloride, 2-methacryloyloxyethylphosphocholine or 3-((3-acrylamidopropyl)dimethylammonium)propionate; wherein the mass concentration of the zwitterion used is 0.1 to 5%.

[0020] Preferably, the grafting time in step (4) is 10 to 150 seconds.

[0021] Preferably, in step (4), the heat treatment temperature is 50 to 90° C., and the heat treatment time is 30 to 300 seconds.

[0022] The invention discloses an anti-pollution reverse osmosis membrane prepared by a method for preparing an anti-pollution reverse osmosis membrane.

[0023] The principle of the present invention is that the active monomer of benzophenone can be used as a photoinitiator, and can subtract H from the polymer under ultraviolet irradiation to form hydrocarbon free radicals, which can stably initiate free radical polymerization and form permanent chemical crosslinks on the surface. 4,4-dihydroxybenzophenone or 4,4-diaminobenzophenone can react with residual acyl chloride on the membrane surface, introduce it into the membrane surface as a photoinitiator, and then graft zwitterions containing double bonds under ultraviolet irradiation to achieve hydrophilic modification of the reverse osmosis membrane surface.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) In the present invention, the photoinitiator is introduced into the film surface by reacting the residual acyl chloride in the newly formed polyamide layer with a photoinitiator containing a phenolic hydroxyl group or an amino group. This process takes a shorter time (within 5 minutes) than the traditional surface activation process and can be carried out continuously after the interfacial polymerization reaction, which is convenient for industrial production.

[0026] (2) The present invention grafts the zwitterionic polymer onto the membrane surface through a photo-initiated free radical polymerization reaction. Compared with the traditional grafting method, the operation is simple and efficient, the reaction time is significantly shortened (within 10 minutes), it is easy to mass produce, and the use of organic solvents in the reaction process is reduced.

[0027] (3) The anti-fouling reverse osmosis membrane grafted with zwitterionic polymer provided by the present invention effectively improves the anti-fouling performance of the reverse osmosis membrane while ensuring membrane flux and salt retention. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The present invention is a flow chart for preparing the anti-pollution polyamide reverse osmosis membrane;

[0029] Figure 2 The infrared spectra and X-ray photoelectron spectra of the anti-pollution polyamide reverse osmosis membrane numbered 4-4 in Example 4 of the present invention and the polyamide reverse osmosis membrane of Comparative Example 1;

[0030] Figure 3 The water contact angle and surface energy of the anti-pollution polyamide reverse osmosis membrane numbered 4-4 in Example 4 of the present invention and the polyamide reverse osmosis membrane of Comparative Example 1;

[0031] Figure 4 The NaCl separation performance of the anti-pollution polyamide reverse osmosis membrane numbered 4-4 in Example 4 of the present invention and the polyamide reverse osmosis membrane of Comparative Example 1;

[0032] Figure 5 The normalized flux and anti-pollution index of the anti-pollution polyamide reverse osmosis membrane No. 4-4 in Example 4 of the present invention and the polyamide reverse osmosis membrane of Comparative Example 1 during the filtration process of bovine serum albumin;

[0033] Figure 6 The normalized flux and anti-pollution index of the anti-pollution polyamide reverse osmosis membrane No. 4-4 in Example 4 of the present invention and the polyamide reverse osmosis membrane of Control Example 1 in the simulated gypsum solution filtration process. DETAILED DESCRIPTION

[0034] In order to make the advantages and technical solutions of the present invention more clear and explicit, the present invention is described in detail below in conjunction with specific embodiments and drawings.

[0035] The raw materials required for the present invention can be purchased through commercial channels.

[0036] The test method of permeation flux and salt retention rate of reverse osmosis membrane: The cross-flow performance evaluation device is used to test the flux and salt retention rate of reverse osmosis membrane. The test system includes pump, membrane pool, pipeline, regulating valve, pressure and flow detector, etc. The effective membrane area tested is 18.2cm 2 , the test pressure is 15 bar, the test temperature is 25±0.5℃. The raw liquid for testing salt retention rate is NaCl (2000ppm). Each membrane sample is pre-pressed for at least 2h before sampling and testing to maintain a stable flux.

[0037] The calculation formula of flux (P) is:

[0038]

[0039] Where P is the flux of the membrane (L·m -2 ·h -1 bar -1 ), V is the volume of water passing through the membrane (L), s is the effective area of ​​the membrane (m 2 ), t is the penetration time (h), and p is the test pressure (bar).

[0040] The calculation formula of retention rate (R) is:

[0041]

[0042] Among them, C p and C f are the salt concentrations of the permeate and feed solution, respectively. The salt concentration is detected by a conductivity meter.

[0043] Method for testing the anti-fouling performance of the reverse osmosis membrane: The anti-fouling performance of the reverse osmosis membrane was tested using the above-mentioned cross-flow reverse osmosis device. During the experiment, the permeate and concentrate were continuously circulated to the feed tank. In the first stage, the membrane was pre-pressed with deionized water at an adjusted pressure for 2 hours to obtain a stable pure water flux (J w0); In the second stage, the deionized water was replaced with the pollutant solution and filtered at the same pressure for 4 hours, and the stable flux (J) of each cycle was recorded. p ); Finally, the fouled membrane was cleaned and the pure water flux (J) was re-measured under the same conditions as in the first stage. w The above steps were repeated twice. The organic and inorganic pollutants used in the test were bovine serum albumin (100 ppm) and simulated gypsum solution (1000 ppm Na2SO4 and 1000 ppm CaCl2). t ), reversible flux decline rate (DR r ) and irreversible flux decline rate (DR ir ) is calculated according to the following formula:

[0044]

[0045] Comparative Example 1

[0046] This comparative example 1 provides a method for preparing a reverse osmosis membrane, comprising the following steps:

[0047] (1) dissolving m-phenylenediamine in water to obtain an aqueous solution having a mass concentration of 5%;

[0048] (2) slowly pouring the aqueous solution prepared in step (1) onto the polysulfone ultrafiltration membrane and soaking it for 3 to 5 minutes, then pouring out the excess aqueous solution and drying the residual aqueous solution on the membrane surface with an air knife;

[0049] (3) dissolving trimesoyl chloride in n-hexane to obtain a trimesoyl chloride oil phase solution with a mass concentration of 0.1%;

[0050] (4) slowly pouring the oil phase solution obtained in step (3) onto the upper surface of the membrane obtained in step (2), interfacial polymerization for 150 seconds to form a cross-linked polyamide separation layer, pouring the residual trimesoyl chloride oil phase solution from the membrane surface, and washing the membrane surface with n-hexane;

[0051] (5) heat treating the membrane obtained in step (4) in an oven at 70° C. for 3 min to obtain a polyamide reverse osmosis membrane;

[0052] The separation performance of the polyamide reverse osmosis membrane prepared by the above method was tested, and its water production flux was 2.3 L·m -2 ·h -1 bar -1 , NaCl rejection was 99.2%.

[0053] Example 1

[0054] like Figure 1As shown, this embodiment 1 provides a method for preparing an anti-pollution reverse osmosis membrane, comprising the following steps:

[0055] (1) Fix the polysulfone base membrane on the plate frame, pour a 5% m-phenylenediamine aqueous solution on the surface of the base membrane and let it stand for 3 to 5 minutes, then pour out the excess aqueous solution, and blow dry the residual aqueous solution on the surface of the base membrane with an air knife;

[0056] (2) pouring a 0.1% mass concentration of trimesoyl chloride oil phase solution onto the membrane surface obtained in step (1), interfacial polymerization for 150 seconds to form a cross-linked polyamide separation layer, pouring off the remaining oil phase solution, and washing the unreacted organic acid chloride monomer with an organic solvent;

[0057] (3) pouring 0.5%, 2%, 4%, 6%, and 8% 4,4-dihydroxybenzophenone aqueous solutions on the surface of the TFC membrane prepared in step (2) to react with the residual acyl chloride for 120 seconds, then pouring out the excess photoinitiator solution and blowing off the water droplets on the surface with an air knife;

[0058] (4) pouring a 3.0% (mass concentration) [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl) ammonium hydroxide aqueous solution on the surface of the membrane obtained in step (3), and irradiating it under ultraviolet light for 120 seconds to graft the zwitterionic polymer, then pouring off the excess zwitterionic aqueous solution and rinsing the membrane surface with deionized water;

[0059] (5) heat treating the membrane obtained in step (4) in an oven at 70° C. for 3 min to obtain a polyamide reverse osmosis composite membrane;

[0060] The anti-fouling polyamide reverse osmosis membrane prepared by the above method was tested for separation performance, and the mass concentrations of 4,4-dihydroxybenzophenone were 0.5%, 2%, 4%, 6%, and 8%, respectively recorded as Examples 1-1 to 1-5. The test results are shown in Table 1:

[0061] Table 1 Separation performance test results of Example 1 and Comparative Example 1

[0062]

[0063] As shown in Table 1, the NaCl retention of the reverse osmosis membrane remained almost unchanged after surface grafting; with the increase of 4,4-dihydroxybenzophenone concentration, the flux first increased and then decreased. The decrease in flux was due to the excessively high concentration of 4,4-dihydroxybenzophenone, which increased the number of hydrophobic benzene rings introduced on the membrane surface, reduced the hydrophilicity of the membrane surface, and increased the water transmission resistance. When the concentration of 4,4-dihydroxybenzophenone was 4%, the flux was 2.2 L·m -2 ·h -1 bar -1, NaCl retention is 98.7%, which is no significant difference from the performance of Control Example 1.

[0064] Example 2

[0065] This embodiment 2 provides a method for preparing an anti-pollution polyamide reverse osmosis membrane with high efficiency photoinitiated polymerization grafted with zwitterions, comprising the following steps:

[0066] (1) Fix the base film on the plate frame, pour a 5% m-phenylenediamine aqueous solution on the surface of the base film and let it stand for 3 to 5 minutes, then pour out the excess aqueous solution, and blow dry the residual aqueous solution on the surface of the base film with an air knife;

[0067] (2) pouring a 0.1% mass concentration of trimesoyl chloride oil phase solution onto the membrane surface obtained in step (1), interfacial polymerization for 150 seconds to form a cross-linked polyamide separation layer, pouring off the remaining oil phase solution, and washing the unreacted organic acid chloride monomer with an organic solvent;

[0068] (3) pouring a 4% mass concentration of 4,4-dihydroxybenzophenone aqueous solution on the surface of the TFC membrane prepared in step (2) to react with the residual acyl chloride for 30 seconds, 60 seconds, 90 seconds, 120 seconds, and 150 seconds respectively, then pouring out the excess photoinitiator solution and blowing off the water droplets on the surface with an air knife;

[0069] (4) pouring a 3.0% (mass concentration) [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl) ammonium hydroxide aqueous solution on the surface of the membrane obtained in step (3), and irradiating it under ultraviolet light for 120 seconds to graft the zwitterionic polymer, then pouring off the excess zwitterionic aqueous solution and rinsing the membrane surface with deionized water;

[0070] (5) heat treating the membrane obtained in step (4) in an oven at 70° C. for 3 min to obtain a polyamide reverse osmosis composite membrane;

[0071] The anti-fouling polyamide reverse osmosis membrane prepared by the above method was tested for separation performance, and the reaction time of 4,4-dihydroxybenzophenone was 30s, 60s, 90s, 120s, and 150s, respectively recorded as Examples 2-1 to 2-5. The test results are shown in Table 2:

[0072] Table 2 Separation performance test results of Example 2 and Control Example 1

[0073]

[0074] As shown in Table 2, the NaCl retention of the reverse osmosis membrane has almost no change after surface grafting; with the increase of the reaction time of 4,4-dihydroxybenzophenone, the flux first increases and then decreases. The decrease in flux is because the reaction time of 4,4-dihydroxybenzophenone is too long, the number of hydrophobic benzene rings introduced on the membrane surface increases, the hydrophilicity of the membrane surface decreases, and the water transmission resistance increases. When the reaction time of 4,4-dihydroxybenzophenone is 120s, the flux is 2.3L·m -2 ·h -1 bar -1 , NaCl retention is 98.7%, which is no significant difference from the performance of Control Example 1.

[0075] Example 3

[0076] This embodiment 3 provides a method for preparing an anti-pollution polyamide reverse osmosis membrane with high efficiency photoinitiated polymerization grafted with zwitterions, comprising the following steps:

[0077] (1) Fix the base film on the plate frame, pour a 5% m-phenylenediamine aqueous solution on the surface of the base film and let it stand for 3 to 5 minutes, then pour out the excess aqueous solution, and blow dry the residual aqueous solution on the surface of the base film with an air knife;

[0078] (2) pouring a 0.1% mass concentration of trimesoyl chloride oil phase solution onto the membrane surface obtained in step (1), interfacial polymerization for 150 seconds to form a cross-linked polyamide separation layer, pouring off the remaining oil phase solution, and washing the unreacted organic acid chloride monomer with an organic solvent;

[0079] (3) pouring a 4% mass concentration of 4,4-dihydroxybenzophenone aqueous solution on the surface of the TFC membrane prepared in step (2) to react with the residual acyl chloride for 120 seconds, then pouring out the excess photoinitiator solution and blowing off the water droplets on the surface with an air knife;

[0080] (4) pouring an aqueous solution of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide with a mass concentration of 1.0%, 2.0%, 3.0%, 4.0%, and 5.0% on the surface of the membrane obtained in step (3), and irradiating the membrane under ultraviolet light for 120 seconds to graft the zwitterionic polymer, then pouring off the excess zwitterionic aqueous solution and rinsing the membrane surface with deionized water;

[0081] (5) heat treating the membrane obtained in step (4) in an oven at 70° C. for 3 min to obtain a polyamide reverse osmosis composite membrane;

[0082] The anti-fouling polyamide reverse osmosis membrane prepared by the above method was tested for separation performance, and the mass concentrations of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide were 1.0%, 2.0%, 3.0%, 4.0%, and 5.0%, respectively, and were recorded as Examples 3-1 to 3-5. The test results are shown in Table 3:

[0083] Table 3 Separation performance test results of Example 3 and Comparative Example 1

[0084]

[0085] As shown in Table 3, the NaCl retention of the reverse osmosis membrane has almost no change after surface grafting; with the increase of the mass concentration of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl) ammonium hydroxide, the flux first increases and then decreases. The decrease in flux is because the mass concentration of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl) ammonium hydroxide is too high, and an additional coating is formed on the membrane surface, which increases the water transmission resistance. When the mass concentration of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl) ammonium hydroxide is 3.0%, the flux is 2.2L·m -2 ·h -1 bar -1 , NaCl retention is 98.8%, which is no significant difference from the performance of Control Example 1.

[0086] Example 4

[0087] This embodiment 4 provides a method for preparing an anti-pollution polyamide reverse osmosis membrane with high efficiency photoinitiated polymerization grafted with zwitterions, comprising the following steps:

[0088] (1) Fix the base film on the plate frame, pour a 5% m-phenylenediamine aqueous solution on the surface of the base film and let it stand for 3 to 5 minutes, then pour out the excess aqueous solution, and blow dry the residual aqueous solution on the surface of the base film with an air knife;

[0089] (2) pouring a 0.1% mass concentration of trimesoyl chloride oil phase solution onto the membrane surface obtained in step (1), interfacial polymerization for 150 seconds to form a cross-linked polyamide separation layer, pouring off the remaining oil phase solution, and washing the unreacted organic acid chloride monomer with an organic solvent;

[0090] (3) pouring a 4% mass concentration of 4,4-dihydroxybenzophenone aqueous solution on the surface of the TFC membrane prepared in step (2) to react with the residual acyl chloride for 120 seconds, then pouring out the excess photoinitiator solution and blowing off the water droplets on the surface with an air knife;

[0091] (4) pouring a 3% (mass concentration) [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl) ammonium hydroxide aqueous solution on the surface of the membrane obtained in step (3), and irradiating the membrane under ultraviolet light for 30s, 60s, 90s, 120s, and 150s, respectively, to graft the zwitterionic polymer, then pouring off the excess zwitterionic aqueous solution and rinsing the membrane surface with deionized water;

[0092] (5) heat treating the membrane obtained in step (4) in an oven at 70° C. for 3 min to obtain a polyamide reverse osmosis composite membrane;

[0093] The anti-fouling polyamide reverse osmosis membrane prepared by the above method was tested for separation performance, and the grafting time of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide was 30s, 60s, 90s, 120s, and 150s, respectively recorded as Examples 4-1 to 4-5. The test results are shown in Table 4:

[0094] Table 4 Separation performance test results of Example 4 and Comparative Example 1

[0095]

[0096] As shown in Table 4, the NaCl retention of the reverse osmosis membrane has almost no change after surface grafting; with the increase of the grafting time of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl) ammonium hydroxide, the flux first increases and then decreases. The decrease in flux is because the grafting time of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl) ammonium hydroxide is too long, and an additional coating is formed on the membrane surface, which increases the water transmission resistance. When the grafting time of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl) ammonium hydroxide is 120s, the flux is 2.3L·m -2 ·h -1 bar -1 , NaCl retention is 99.1%, which is no significant difference from the performance of Control Example 1.

[0097] Example 5

[0098] This embodiment 5 provides a method for preparing a highly efficient photo-initiated polymerization-grafted zwitterion-resistant polyamide reverse osmosis membrane, comprising the following steps:

[0099] (1) Fix the base film on the plate frame, pour a 5% m-phenylenediamine aqueous solution on the surface of the base film and let it stand for 3 to 5 minutes, then pour out the excess aqueous solution, and blow dry the residual aqueous solution on the surface of the base film with an air knife;

[0100] (2) pouring a 0.1% mass concentration of trimesoyl chloride oil phase solution onto the membrane surface obtained in step (1), interfacial polymerization for 150 seconds to form a cross-linked polyamide separation layer, pouring off the remaining oil phase solution, and washing the unreacted organic acid chloride monomer with an organic solvent;

[0101] (3) pouring a 1% 4,4-diaminobenzophenone ethanol solution onto the surface of the TFC membrane prepared in step (2) to react with the residual acyl chloride for 120 seconds, then pouring out the excess photoinitiator solution and blowing off the water droplets on the surface with an air knife;

[0102] (4) pouring a 3% (mass concentration) [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl) ammonium hydroxide aqueous solution on the surface of the membrane obtained in step (3), and irradiating it under ultraviolet light for 120 seconds to graft the zwitterionic polymer, then pouring off the excess zwitterionic aqueous solution and rinsing the membrane surface with deionized water;

[0103] (5) heat treating the membrane obtained in step (4) in an oven at 70° C. for 3 min to obtain a polyamide reverse osmosis composite membrane;

[0104] The separation performance of the polyamide reverse osmosis membrane prepared by the above method was tested, and its water production flux was 2.4 L·m -2 ·h -1 bar -1 , NaCl rejection was 99.3%.

[0105] like Figure 2 As shown, the anti-fouling polyamide reverse osmosis membrane numbered 4-4 in the above Example 4 and the polyamide reverse osmosis membrane of Control Example 1 were characterized by infrared and XPS. Figure 2 (a) is the infrared spectrum of the reverse osmosis membrane, from which it can be seen that compared with the polysulfone bottom membrane, all reverse osmosis membranes have a -1 、1608cm -1 and 1663cm -1 The NH in-plane bending vibration, NH deformation vibration and C=O stretching vibration peaks appeared at 1725 cm -1 The peak at 1039cm is the stretching vibration of the ester group formed by the phenolic hydroxyl group and the acyl chloride, indicating that 4,4-dihydroxybenzophenone reacted with trimesoyl chloride and successfully introduced 4,4-dihydroxybenzophenone into the membrane surface. -1 The peak at is attributed to the stretching vibration of -SO3-, indicating that the zwitterionic polymer was successfully grafted onto the membrane surface. Figure 2 (b) is the XPS spectrum of the reverse osmosis membrane, from which we can see the S element signal appearing in the anti-fouling reverse osmosis membrane, proving that the zwitterions were successfully grafted.

[0106] like Figure 3 As shown, the anti-fouling polyamide reverse osmosis membrane No. 4-4 in the above Example 4 and the polyamide reverse osmosis membrane of Control Example 1 were tested for surface wettability and surface energy. Compared with Control Example 1, the anti-fouling reverse osmosis membrane grafted with zwitterions has enhanced hydrophilicity and increased surface energy, which is caused by the grafted hydrophilic zwitterions.

[0107] like Figure 4 As shown, the performance of the anti-fouling polyamide reverse osmosis membrane No. 4-4 in Example 4 was compared with the performance of the polyamide reverse osmosis membrane of Control Example 1. The flux interception of the anti-fouling polyamide reverse osmosis membrane obtained in Example 4-4 was not reduced, which ensured the good separation performance of the polyamide reverse osmosis membrane.

[0108] The anti-pollution performance of the anti-pollution polyamide reverse osmosis membrane No. 4-4 in the above Example 4 and the polyamide reverse osmosis membrane of the comparative example 1 were tested for organic pollutant anti-pollution performance. The results are as follows: Figure 5 shown. Figure 5 (a) is the normalized flux of the reverse osmosis membrane during the filtration of bovine serum albumin, Figure 5 (b) is the anti-fouling index of the reverse osmosis membrane. Figure 5 It can be seen that the anti-fouling polyamide reverse osmosis membrane obtained in Example 4-4 has a significantly better anti-organic pollution effect than the polyamide reverse osmosis membrane obtained in Control Example 1. The reason is that the grafting of zwitterionic polymers on the membrane surface can effectively improve the hydrophilicity of the membrane surface, build a stable hydration layer on the membrane surface, increase the Gibbs free energy of pollutant deposition on the membrane surface, and thus inhibit the deposition of pollutants on the membrane surface; in addition, the improvement of the hydrophilicity of the membrane surface effectively inhibits the hydrophobic interaction between the membrane surface and pollutants, and reduces the adsorption of pollutants on the membrane surface.

[0109] The anti-pollution performance of the anti-pollution polyamide reverse osmosis membrane No. 4-4 in the above Example 4 and the polyamide reverse osmosis membrane of the comparative example 1 were tested for inorganic pollutant anti-pollution performance. The results are as follows: Figure 6 shown. Figure 6 (a) is the normalized flux of the reverse osmosis membrane during the simulated gypsum solution filtration process, Figure 6 (b) is the anti-fouling index of the reverse osmosis membrane. Figure 6 It can be seen that the anti-fouling polyamide reverse osmosis membrane obtained in Example 4-4 has a significantly better anti-inorganic pollution effect than the polyamide reverse osmosis membrane obtained in Control Example 1. The reasons are: the more hydrophilic membrane surface increases the energy barrier of heterogeneous nucleation, making it difficult for pollutant aggregates to form on the membrane surface; in addition, the presence of the hydration layer on the membrane surface reduces the Ca 2+ The complexation with -COOH groups reduces the possibility of forming a contamination layer.

[0110] The parts not mentioned above can be realized by referring to the existing technology.

[0111] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by technicians in this technical field within the essential scope of the present invention should also fall within the protection scope of the present invention.

Claims

1. A method for preparing an anti-pollution reverse osmosis membrane, characterized in that: The method of rapidly grafting zwitterionic polymers on the membrane surface by photoinitiated polymerization reaction comprises the following steps: (1) Fixing the base film on the plate frame, applying the organic amine aqueous monomer solution on the surface of the base film and letting it stand, then pouring out the excess aqueous solution, and blowing the residual aqueous solution on the surface of the base film dry with an air knife; (2) pouring the organic acid chloride oil phase solution onto the membrane surface obtained in step (1) to carry out interfacial polymerization reaction to form a cross-linked polyamide separation layer, pouring out the residual oil phase solution, and washing the unreacted organic acid chloride monomer with an organic solvent; (3) pouring a photoinitiator solution onto the surface of the film prepared in step (2) to react with the residual acyl chloride, then pouring off the excess photoinitiator solution and blowing off the water droplets on the surface with an air knife; (4) pouring a zwitterionic aqueous solution onto the membrane surface obtained in step (3), and irradiating the grafted zwitterionic polymer under ultraviolet light, then pouring off the excess zwitterionic aqueous solution, and washing the membrane surface with deionized water; (5) The membrane obtained in step (4) is heat-treated in an oven to obtain an anti-pollution polyamide reverse osmosis membrane.

2. The method for preparing an anti-pollution reverse osmosis membrane according to claim 1, characterized in that: In the step (1), the organic amine aqueous phase monomer is m-phenylenediamine, and the standing time is 3 to 5 minutes; wherein the mass concentration of the m-phenylenediamine used is 0.1 to 10%.

3. The method for preparing an anti-pollution reverse osmosis membrane according to claim 1, characterized in that: In the step (1), the base membrane is one of a polysulfone ultrafiltration membrane, a polyethersulfone ultrafiltration membrane, a polyimide ultrafiltration membrane, a polyacrylonitrile ultrafiltration membrane, a polyethylene ultrafiltration membrane or a polypropylene ultrafiltration membrane.

4. The method for preparing an anti-pollution reverse osmosis membrane according to claim 1, characterized in that: In the step (2), the organic acid chloride is at least one of trimesoyl chloride, terephthaloyl chloride, phthaloyl chloride, pyromellitoyl chloride, malonyl chloride, glutaryl chloride, and fumaryl chloride; the organic solvent is at least one of n-hexane, cyclohexane, n-heptane, toluene, Isopar-G, Isopar-E, Isopar-H, Isopar-L, and Isopar-M; the mass concentration of the organic acid chloride oil phase solution is 0.01-2%; and the polymerization reaction time is 10-300s.

5. The method for preparing an anti-pollution reverse osmosis membrane according to claim 1, characterized in that: In the step (3), the photoinitiator is at least one of benzophenone-type photoinitiators such as benzophenone, 4-hydroxybenzophenone, 4-aminobenzophenone, 4,4-dihydroxybenzophenone or 4,4-diaminobenzophenone; wherein the mass concentration of the photoinitiator used is 0.1 to 10%.

6. The method for preparing an anti-pollution reverse osmosis membrane according to claim 1, characterized in that: In the step (3), the reaction time of the photoinitiator and the acyl chloride is 10 to 150 seconds.

7. The method for preparing an anti-pollution reverse osmosis membrane according to claim 1, characterized in that: In the step (4), the zwitterion is at least one of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonatepropyl)ammonium hydroxide, methacryloyloxyethyltrimethylammonium chloride, 2-methacryloyloxyethylphosphocholine or 3-((3-acrylamidopropyl)dimethylammonium)propionate; wherein the mass concentration of the zwitterion used is 0.1 to 5%.

8. The method for preparing an anti-pollution reverse osmosis membrane according to claim 1, characterized in that: The grafting time in step (4) is 10 to 150 seconds.

9. The method for preparing an anti-pollution reverse osmosis membrane according to claim 1, characterized in that: In the step (4), the heat treatment temperature is 50 to 90° C., and the heat treatment time is 30 to 300 seconds.

10. An anti-pollution reverse osmosis membrane prepared by the method for preparing an anti-pollution reverse osmosis membrane according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Hydrophilic bactericidal anti-contamination reverse osmosis membrane and preparation method thereof

    CN108057348A

  • Polytetrafluoroethylene-based composite nanofiltration membrane as well as preparation method and application thereof

    CN118403510A

  • Preparation method of zwitterion-fluorine functionalized anti-pollution polyamide composite membrane

    CN118788155A

  • Draw solute for forward osmosis, forward osmosis water treatment device, and forward osmosis method for water treatment

    US20140217026A1

  • Chemically and UV cross-linked high selectivity polyimide membranes for gas separations

    US20180050310A1

Cited By

  • Pollution-resistant polyamide composite membrane and preparation method thereof

    CN121401895A

  • Reverse osmosis membrane with gradient cross-linked structure and preparation method of reverse osmosis membrane

    CN121911236A